The Immunology of Takotsubo Syndrome - Lim, Kenji Rowel Q.; Mann, Douglas L.; Kenzaka, Tsuneaki; Hayashi, Tomohiro (Frontiers in Immunology, 2023)
Takotsubo syndrome (TTS) is a disorder characterized by transient cardiac dysfunction with ventricular regional wall motion abnormalities, primarily thought to be caused by the effects of a sudden catecholamine surge on the heart. Although the majority of patients exhibit prompt recovery of their cardiac dysfunction, TTS remains associated with increased mortality rates acutely and at long-term, and there is currently no cure for TTS. Inflammation has been shown to play a key role in determining outcomes in TTS patients, as well as in the early pathogenesis of the disorder. There are also cases of TTS patients that have been successfully treated with antiinflammatory therapies, supporting the importance of the inflammatory response in TTS. In this article, we provide a comprehensive review of the available clinical and pre-clinical literature on the immune response in TTS, in an effort to not only better understand the pathophysiology of TTS but also to generate insights on the treatment of patients with this disorder.